Penerapan Model Inkuiri Terbimbing Berbasis Education for Sustainable Development untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMP - Marisha Silta Fany; Neng Sholihat; Defrizal Hamka (International Forum of Researchers and Lecturers, 2024)
The main objective of this study was to determine the extent to which students' critical thinking skills can be improved through the implementation of a guided inquiry learning model based on Education for Sustainable Development (ESD). This study used a quasi-experimental approach with a post-test only control group design. The study population consisted of 5 classes with a total of 190 students. From this population, the researcher took a sample of 68 students through a simple random sampling technique. The sample was then divided into two groups, namely 34 students for the experimental class and 34 students for the control class. The research instrument was a critical thinking skills test consisting of 20 objective, reasoned questions. The research data were analyzed using a t-test. Based on the calculation results, the t-value was 3.792, while the t-table value at a significance level of 0.05 was 2.037. This indicates that Ha is accepted and Ho is rejected. Thus, there is a significant difference between the critical thinking skills of students who participated in learning with a guided inquiry model based on ESD compared to conventional learning. In addition, the improvement in critical thinking skills was also analyzed through the N-Gain calculation. The results showed that the experimental class achieved a 65% improvement, categorized as moderate, while the control class achieved a 59% improvement, also categorized as moderate. These findings indicate that guided inquiry learning integrated with ESD principles provides a more effective way to foster students' critical thinking skills compared to traditional methods. Therefore, ESD-based guided inquiry learning can be an alternative, innovative learning strategy to improve the quality of the learning process in secondary schools.